CLIMATE CHANGE: CAUSES AND POSSIBLE SOLUTIONS - Laddha, Abha (International Journal of Research -GRANTHAALAYAH, 2015)
Global climatic changes because of human activities have become a major threat to life on Earth. Changing climatic conditions are the result of man-made activities and are continuously leading to a serious deterioration in the earth’s atmosphere. Basically it is leading to erratic climate and weather extremes, altered ecosystems and habitats and risks to human health and society. This problem can be solved only if some judicious steps are taken, including improvements to energy efficiency and vehicle fuel economy, increases in wind and solar power, hydrogen produced from renewable sources, biofuels (produced from crops), natural gas, and nuclear power.